Impact of heat processing on nutritional and functional properties of peach - Oliveira, Ana L. (2017)
Peach is a fruit with high content of phytochemical compounds with antioxidant activity, namely polyphenols and carotenes that make them a healthy fruit for consumers. Peach (Prunus persica (L.)), is an important commercial Mediterranean fruit during summer season not only for its high water content, fibre and minerals, but also for its high content in antioxidant molecules such as procyanidins, anthocyanins, catechins, phenolic acids and carotenoids (lutein, zeaxanthin, β-cryptoxanthin and β-carotene). These compounds in peach fruit vary strongly in relation to different environmental and agricultural factors, such as cultivar, rootstock, water and ripening stage at harvest. Besides the regular peach consumption as fresh fruit, processed products such as juices, jams, jellies, smoothies, canned fruit and others, are usually produced from fruit fresh market. Information about nutrient content of processed fruits is of interest to consumers as they are becoming more aware and interested about their related health benefits. Fruit processing and storage may lead to negative or positive effects concerning their nutritional value according the processing steps they are exposed to. There are occurrences during fruit processing where chemical reactions could release bound components leading to a promotion of nutritional quality. Among the phytochemicals, phenols, have received a great deal of attention because of their antioxidant activity, which help to neutralise free radicals. Thermal treatment is one of the most important factors affecting their stability. Previous studies have shown that concentrations of carotenoids often increase during heat treatment, probably because cell walls are softened, making the extraction of carotenoids easier during analysis. Extreme or prolonged heat treatment, however, enhances loss of carotenoids. Factors such as light, metals, oxygen, organic acids and heat can promote carotenoid isomerization and degradation. The aim of this chapter, therefore, is to review the impact of different industrial processing techniques of sterilization and associated storage conditions (e.g., time and temperature) on nutritional and functional characteristics of processed peach, and to establish their role on the nutritional and functional quality of fruit.